Perhitungan Harga Pokok Produksi dengan Metode Full Costing untuk Menentukan Harga Jual Minuman Boba Brown Sugar pada Brand “Meenum” - Sari Ayu; Suroso Suroso; Reza Agustur; Fadillah Ashary (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
It is important to pay attention to the calculation of the cost of production, due to increasing competition between businesses, creating quality products at fairly competitive prices. This research aims to determine the calculation of the cost of production in determining the selling price of Boba Brown Sugar beverage products under the "Meenum" brand. The Full Costing method is a method of determining the cost of a product that takes into account all elements of production costs consisting of raw materials, direct labor costs and factory overhead costs, both fixed and variable. The selling price is obtained from the cost of production plus expected profit. With secondary data from the "Meenum" Brand beverage business. The results of the research state that the calculation of the cost of production produces a difference that influences the determination of the selling price.